17Î‘-METHYLTESTOSTERONE (ANABOLIC ANDROGENIC STEROIDS) ALTERS ACETYLCHOLINESTERASE ENZYME ACTIVITY IN DIFFERENT PARTS OF THE BRAIN IN FEMALE MICE, MUS MUSCULUS - B Patil, Sachin; S Inamdar, Laxmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim: Anabolic androgenic steroids (AAS) are synthetic derivatives of the male sex hormone testosterone. Androgens and anabolic steroids have been used for therapeutic purpose with few exceptions. However, the abuse of AAS is a remarkably prevalent problem, particularly among athletes and adolescents. Supraphysiological doses of AAS exert profound effects on mental state and behaviors such as depression, anxiety, aggressiveness, and cognitive deterioration. Objective: In the present investigation, we studied the impact of one of the AAS compounds, i.e., 17Î±-methyltestosterone on acetylcholinesterase (AChE) enzyme activity in different brain parts of mice, namely, forebrain, hippocampus, midbrain, and hindbrain. Methods: The adult female mice were assigned to four experimental groups to which different doses of 17Î±-MT (0.5, 5.0 and 7.5 mg/kg bwt, respectively) were administrated s.c. for 30 days. A significant increase in AChE activity in forebrain and midbrain (low and medium dose treatment) suggests a reduction of cholinergic neurotransmission efficiency due to decrease in acetylcholine levels in trans-synaptic cleft. Further, concurrent reduction in AChE activity was observed in whole brain, hippocampus, and hindbrain of 17Î±-MT-treated mice suggests the impairment in neuronal transmission. Since the regulation of cholinergic system through acetylcholine hydrolysis has been largely attributed to AChE activity, a significant reduction in its activity may lead to stress-related anxiety, memory loss with some cognitive and behavioral aspects in the mice. Conclusion: Based on the observed results, we propose that 17Î±-MT, an alkylated steroid compound, has a negative impact on AChE enzyme activity in different parts of mice brain, leading to impairment in neuronal transmission.